Two New Species of Eschweilera (Lecythidaceae) from rainforest on the Caribbean slope of Panama - Batista G., Juvenal E.; Mori, Scott A. (Phytotaxa, 2017)
Eschweilera donosoensis and Eschweilera rotundicarpa are described from the lowlands rainforest and cloud forest of the Caribbean slope of Panama. E. donosoensis is common in the lowland rainforests in the Donoso District, Colón Province and E. rotundicarpa is endemic to cloud forest in the General De División Omar Torrijos Herrera National Park, Coclé Province and also the lowland rainforest of Valle Grande in the Donoso District, Colón Province. In this paper these species are illustrated, and information on distribution, habitat, ecology, phenology and conservation status according to IUCN are provided.